2010
DOI: 10.1165/2009-0147oc
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Agonists Ameliorate Sodium and Fluid Transport and Inflammation in Cystic Fibrosis Airway Epithelial Cells

Abstract: The metabolic sensor AMP-activated kinase (AMPK) inhibits both the cystic fibrosis (CF) transmembrane conductance regulator (CFTR) Cl -channel and epithelial Na 1 channel (ENaC), and may inhibit secretion of proinflammatory cytokines in epithelia. Here we have tested in primary polarized CF and non-CF human bronchial epithelial (HBE) cells the effects of AMPK activators, metformin and 5-aminoimidazole-4-carboxamide-1-b-D-riboside (AICAR), on various parameters that contribute to CF lung disease: ENaC-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
69
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 50 publications
(68 reference statements)
4
69
1
Order By: Relevance
“…We report that P. aeruginosa elicited a more robust increase in cytokine and chemokine expression (e.g., IL-8, CXCL1, CXCL2, and TNF-␣) in CFBE-wt-CFTR cells compared with CFBE-⌬F508-CFTR cells. These data add to a growing body of evidence revealing that the inflammatory response of human airway epithelial cells expressing wt-CFTR and ⌬F508-CFTR to P. aeruginosa is model dependent, even when considering matched cell lines and human airway epithelial cells in primary culture (4,6,8,16,18,22,26,28,31,37,39,41). Taken together with other published studies, our data demonstrate that there is no compelling evidence to support the view that mutations in CFTR induce a hyperinflammatory response in human airway epithelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…We report that P. aeruginosa elicited a more robust increase in cytokine and chemokine expression (e.g., IL-8, CXCL1, CXCL2, and TNF-␣) in CFBE-wt-CFTR cells compared with CFBE-⌬F508-CFTR cells. These data add to a growing body of evidence revealing that the inflammatory response of human airway epithelial cells expressing wt-CFTR and ⌬F508-CFTR to P. aeruginosa is model dependent, even when considering matched cell lines and human airway epithelial cells in primary culture (4,6,8,16,18,22,26,28,31,37,39,41). Taken together with other published studies, our data demonstrate that there is no compelling evidence to support the view that mutations in CFTR induce a hyperinflammatory response in human airway epithelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 47%
“…Although it is generally assumed that CF airway epithelial cells are hyperinflammatory in response to P. aeruginosa compared with non-CF airway epithelial cells, human CF airway cells in culture often fail to show a hyperinflammatory phenotype compared with airway epithelial cells expressing wild-type (wt)-CFTR (16,21,35). Indeed, one-third of published studies reveal that CF airway cells elaborate a more robust increase in IL-8 production than non-CF cells in response to P. aeruginosa (28,37,39,41), one-third report no difference (4,6,8,16,26), and one-third actually report that wt-CFTR cells release more IL-8 than CF cells in response to P. aeruginosa (18,22,31). Moreover, because the lungs during infection with P. aeruginosa contain immune cells that, like airway epithelial cells, produce cytokines and chemokines, it is not possible to determine whether the cytokines and chemokines in vivo originate from immune cells and/or airway epithelial cells.…”
mentioning
confidence: 99%
“…In order to mechanistically characterize the observed phenomena, the authors assayed the activity of three kinases that might be involved in regulation of ENaC activity and found that caffeine did not change the abundance of SGK1, ERK1/2 or PKCα, but rather dosedependently decreased phosphorylation and abundance of AMPKα. Earlier findings by others also revealed that AMPK activation can decrease ENaC-mediated sodium current in mouse collecting ducts and airway epithelial cell lines (15,16). The reported data is an excellent confirmation of the idea that downregulation of ENaC is beneficial during SS hypertension, and chronic caffeine consumption may be one of the factors facilitating a reduction in ENaC function and/or expression.…”
supporting
confidence: 78%
“…Consequently, we examined the hypothesis that adenosine monophosphate-activated kinase (AMPK), a key cellular energy sensor and regulator, may contribute to the anti-inflammatory effects of TZDs. We considered a role for AMPK because (1) TZDs can activate AMPK (26,27), and (2) the activation of AMPK by 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR) or by metformin inhibits inflammatory cytokine production from other cell types (28)(29)(30)(31)(32)(33)(34). In vivo, AICAR is also effective at alleviating inflammation in experimental murine colitis (35) and models of asthma (36).…”
mentioning
confidence: 99%